PENGARUH PENGALAMAN PETANI DAN PENGARUH ORANG LAIN TERHADAP ADOPSI MESIN TANAM RICE TRANSPLANTER DI KECAMATAN MOJOLABAN KABUPATEN SUKOHARJO - Catur Munawaroh; Suminah Suminah; Hanifah Ihsaniyati (Universitas Sebelas Maret, 2019)
This research aimed to observe the farmer’s experience, other people’s influence, farmer’s attitude to the adoption of rice transplanter planting machine and farmer’s adoption to the rice transplanter planting machine is Mojolaban Sub-district of Sukoharjo District and to observe the effect of farmer’s experience, other people’s influence and attitude in partially and simultaneously to the adoption of rice transplanter planting machine in Mojolaban Sub-district of Sukoharjo District. The basic method used was qualitative. The research location was determined as purposive in Mojolaban District. The sampling was done using proportional random sampling research method with the number of 60 respondents. The data collection technique was using observation, interview, and documentation. The data analysis method was using path analysis method.The research result showed that farmer’s experience in Mojolaban Sub-district was low, other people’s influence was rare, farmer’s attitude to the adoption of rice transplanter planting machine was disagree and farmer’s adoption to the rice transplanter planting machine was never adopt. Partially, farmer’s experience significantly effected to the adoption of rice transplanter planting machine directly greater than the attitude, the influence of other people has no significant effect on the adoption of rice transplanter planting machines and the attitude of farmers has a significant effect on the adoption of rice transplanter planting machines in Mojolaban District, Sukoharjo Regency. Farmer’s experience, other people’s influence and attitude simultaneously significantly affected to the adoption of rice transplanter planting machine in Mojolaban Sub-district of Sukoharjo District.